Re-imagining the region. (February 2015) - Collits, Paul; Rowe, James E
Traditionally, regional policy has sought to intervene 'in place'. There have been many critiques of particular policies and regional strategies, and a more sustained critique of regional policy more generally, based upon the complexity of regional processes and the relative incapacity of governments to control, or in some cases even to influence, these processes and deliver the outcomes they desire. In the 21st century, there are new and even more complicating processes – the new globalisation, greater mobility, new kinds of mobility, the increased openness of borders, rapidly shifting business models, accelerating disruption of industries and businesses by new start-ups, and distributed work – that render much thinking, strategy and policy related to regions obsolete. This paper describes some of these processes, what they mean for policy and, even more fundamentally, what they mean for the way we think about regions.